Фемінність та маскулінність як чинник тендерної поляризації - Ващенко, К. С. (ХНУРЕ, 2023)
This article discusses stereotypes related to gender identity and the problems that can arise in people's lives due to these cliches. It emphasizes the need to reject gender-based models of behavior and describes how this can help achieve a more equitable society.